DISTRIBUTIVE AND SELF-SUSTAINABLE SCHEDULING ALGORITHMS FOR WIRELESS SENSOR NETWORKS - SHEIKH, MUHAMMAD AMAN (2013)
Wireless Sensor Networks (WSNs), due to their vital importance, are emerging as a ubiquitous networking arena which pervades some of the old applications and also enables many new ones. The credit for the rapid growth in WSN technology goes to its self-organising and self-configuring abilities. Generally, the distributed environment ofWSNs with little or no predetermined infrastructure, mobility, lack of bandwidth and scalability are the issues that affect network performance. In WSNs, lifetime is considered as the key challenging issues because all of the sensors are battery powered. Physically, it is infeasible to recharge or replace the battery. Most of the energy in WSN is wasted due to idle listening, collision, message overhearing, and message overhead.